2023
DOI: 10.1021/acs.analchem.3c00366
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Interfering Ions Using Ion Flux Phenomena in Flow-Through Cl-ISEs with Ion Exchange Membranes

Abstract: Ion-selective electrodes (ISEs) are among the most successful electrochemical sensors used in various applications because of their ability to measure electrolyte concentrations in liquids easily. It is common practice to suppress ion fluxes through the ion-sensitive membranes in ISEs because such fluxes worsen the lower limit of detection. In this study, we propose a method to detect interfering ions using this ion flux phenomenon. As a proof of principle, a flow-type Cl-ISE based on an ion exchange membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…It has previously been shown that CNDs may be utilized as a fluorescent probe for detecting metal ions with an ultra-low detection limit (ppm level) (e.g., Hg 2+ , Pb 2+ , Fe 3+ , and so on) [ 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. CND fluorescence quenching may be used as an in-situ approach to detect metallic ions in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that CNDs may be utilized as a fluorescent probe for detecting metal ions with an ultra-low detection limit (ppm level) (e.g., Hg 2+ , Pb 2+ , Fe 3+ , and so on) [ 17 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. CND fluorescence quenching may be used as an in-situ approach to detect metallic ions in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%